Immunohistochemical expression of cyclooxygenase-2 in oral squamous cell carcinoma - Nirupa Thomas; Rekha Krishnapillai; P Ramakrishnan Bindhu; Priya Thomas (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: Oral cancer is a major health problem in South East Asia. The immunohistochemical (IHC) overexpression of COX-2 in squamous cell carcinoma is well documented. This IHC study was undertaken to understand the COX-2 expression in different grades of oral squamous cell carcinoma (OSCC) and to compare the COX-2 expression in OSCC and normal mucosa. Material and Methods: A total of 30 cases of OSCC and 10 cases of normal mucosa and positive control colon cancer were studied for IHC expression of COX-2. Of the 30 cases studied 10 cases each of well, moderately and poorly differentiated carcinoma were studied. COX-2 staining was evaluated on the basis of presence or absence of the positive tumor cells and percentage of positive tumor cells. Statistical Analysis: The various statistical tests used in this study were t-test and Chi-square test which was carried out using SPSS for Windows 22.0.0 and Minitab version 17.1.0 software package. Results: There was significant increase in COX-2 staining intensity from well to poorly differentiated OSCC. Significant difference was observed in staining intensity between moderately and poorly differentiated SCC. The percentage of positive tumor cells were high in poorly differentiated SCC compared to well and moderately differentiated OSCC. No significant expression of COX-2 was noted in normal mucosa. Interpretation and Conclusion: Our results revealed that the COX-2 enzymes were expressed, suggesting that they play complementary roles during oral carcinogenesis. In near future researches on administration of chemoradiation therapy combined with COX-2 should be evaluated to improve therapy response.